2013
DOI: 10.1261/rna.039669.113
|View full text |Cite
|
Sign up to set email alerts
|

Minotaur is critical for primary piRNA biogenesis

Abstract: Piwi proteins and their associated small RNAs are essential for fertility in animals. In part, this is due to their roles in guarding germ cell genomes against the activity of mobile genetic elements. piRNA populations direct Piwi proteins to silence transposon targets and, as such, form a molecular code that discriminates transposons from endogenous genes. Information ultimately carried by piRNAs is encoded within genomic loci, termed piRNA clusters. These give rise to long, single-stranded, primary transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 54 publications
0
51
0
Order By: Relevance
“…Genetic mouse studies have also revealed that the intact CB is not required for piRNA production (Tanaka et al 2011). Moreover, the initial steps of primary piRNA biogenesis are compartmentalized on the surface of the mitochondria that contain the conserved primary piRNA components, including GAZS, GPAT2, and endoribonuclease Zucchini/ PLD6 (Ma et al 2009;Huang et al 2011;Watanabe et al 2011;Ipsaro et al 2012;Nishimasu et al 2012;Czech et al 2013;Handler et al 2013;Shiromoto et al 2013;Vagin et al 2013). These proteins were not detected in the CB pulldowns.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic mouse studies have also revealed that the intact CB is not required for piRNA production (Tanaka et al 2011). Moreover, the initial steps of primary piRNA biogenesis are compartmentalized on the surface of the mitochondria that contain the conserved primary piRNA components, including GAZS, GPAT2, and endoribonuclease Zucchini/ PLD6 (Ma et al 2009;Huang et al 2011;Watanabe et al 2011;Ipsaro et al 2012;Nishimasu et al 2012;Czech et al 2013;Handler et al 2013;Shiromoto et al 2013;Vagin et al 2013). These proteins were not detected in the CB pulldowns.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular functions of protein components of Yb bodies remain largely unknown. Additionally, Zuc, as well as other proteins with unknown functions required for piRNA biogenesis, such as GASZ and Minotaur (mino), are anchored on the mitochondrial surface [9193], suggesting that mitochondria also play a key role in piRNA precursor processing. The interplay between Yb bodies and mitochondria merits further investigation.…”
Section: Pirna Biogenesis In the Cytoplasmmentioning
confidence: 99%
“…MitoPLD/Zucchini, a mitochondrial outer-membrane protein, is a candidate nuclease involved in the processing of piRNA precursors or intermediates (Haase et al, 2010; Huang et al, 2011; Ipsaro et al, 2012; Murota et al, 2014; Nishimasu et al, 2012; Saito et al, 2010; Watanabe et al, 2011a). The piRNA biogenesis factors GASZ and GPAT2/Minotaur are also found in the mitochondrial outer-membrane (Czech et al, 2013; Handler et al, 2013; Ma et al, 2009; Shiromoto et al, 2013; Vagin et al, 2013), suggesting a link between the mitochondrial outer-membrane and piRNA biogenesis. Biochemical analysis is needed to determine the functions of these conserved factors in primary piRNA biogenesis.…”
Section: Primary Pirna Biogenesismentioning
confidence: 99%